African development trends: lessons learnt from the global financial crisis - Kathrin Berensmann (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
2011 has been an important year for Africa. It marked the 50th anniversary of independence for 17 African countries and the 10th anniversary of the Millennium Declaration. It has also been around a decade since steps toward creating the AU und NEPAD were taken. In a series of DIE Briefing Papers,researchers from Europe and Africa look into African Developments a decade after the revival of the African Agenda to take stock and identify the challenges facing the continent in the years to come. Contrary to initial expectations, the global financial crisis has had relatively little impact on most sub-Saharan African countries, unlike other regions of the world. While the consequences for most of these countries in terms of economic growth, exports and capital flows have been low, it remains unclear how serious the humanitarian consequences of the crisis have been, since the effects on the achievement of the Millennium Development Goals, for example, will become apparent only with something of a time-lag, and appropriate data are not yet available. Despite the relatively limited impact of the crisis, sub-Saharan Africa remains particularly susceptible to a variety of exogenous shocks, such as volatile raw material prices, natural disasters and currency fluctuations, which occur more frequently in developing countries than in industrialised countries. This is due to major structural weaknesses, especially a lack of diversification in the structure of the economy and exports and the dominance of primary commodities. The adverse effects of exogenous shocks are more pronounced in low-income countries, a category to which most countries of the region belong. Inadequate social systems and underdeveloped financial and capital markets mean that they have neither suitable instruments for cushioning exogenous shocks, nor the capacity to mobilise sufficient internal resources to finance them. The greatest economic challenge in the medium term is therefore to install suitable economic policy instruments that can be used preventively to cushion exogenous shocks. These internal measures include a sound fiscal policy and effective debt management, the expansion of social protection systems and the long-term diversification of exports. The poorer sections of the population are particularly hard hit by exogenous shocks. This is primarily true of energy and food price shocks, because the poor spend a large proportion of their disposable income on food and energy. What is needed now, then, is the development of suitable institutions to absorb exogenous shocks, like the African Development Bank's Food Emergency Facility, and such social policy instruments as expanded cash transfer programmes. At international level there should be better regulation and supervision of speculation in raw materials to prevent extreme price fluctuations. The G20 have proposals for solving this problem on their agenda.
Keywords: 330